Modificações na prevalência de asma e atopia em escolares de uma região de Porto Alegre - RS - Schuh, Camila Aparecida Zimmermann (2014)
Introduction: A significant increase in the prevalence of asthma and atopy was observed in epidemiological studies conducted in 1980, 1989 and 1998, with school of Porto Alegre. The continuity of this phenomenon in recent decades needed to be evaluated. Objective: Verify the changes in prevalence of symptoms of active and cumulative asthma and atopy in schoolchildren from a region of Porto Alegre. Methodology: In a cross-sectional study in which schoolchildren from 5th to 8th grade (10-18 years), four schools located in the same geographic area were interviewed. The first questionnaire covered symptoms suggestive of asthma (at some point in life or in the last twelve months) and the second was the ACT (test asthma control). In addition, skin tests were performed in 241 schoolchildren. Results: 964 students were interviewed a total of 1195 registered. The age of participants ranged from 10 to 18 years with a mean of 13.3 years. The cumulative prevalence of asthma symptoms was found to be 41,7%, symptoms of active asthma 19,9% and atopy 52,7%. Compared to previous studies, a stabilization in the cumulative prevalence of asthma and atopy occurred while decreased the prevalence of symptoms of active asthma from 22% to 14.9%. (P <0.001) Conclusions: In the last decade the prevalence of symptoms of asthma and atopy cumulative stabilized, with a reduction in the prevalence of symptoms of active asthma in the last year. This finding may help guide the search for environmental factors that are responsible for the manifestation of asthma in genetically susceptible individuals.